2007
DOI: 10.4049/jimmunol.178.12.7814
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cδ Regulates Antigen Receptor-Induced Lytic Granule Polarization in Mouse CD8+ CTL

Abstract: T cell receptor (TCR)‐induced activation of protein kinase C (PKC) has long been known to be critical for regulation of granule exocytosis mediated cytotoxicity in CD8+ T cells. However, the mechanism by which PKC regulates this effector function is not clear. In addition, it is not known which PKC family members are involved in the regulation of this process. By combining the use of pharmacological inhibitors and mice with targeted gene deletions, we showed that Protein Kinase C □elta is required for granule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 44 publications
4
44
1
2
Order By: Relevance
“…Although the inclusion recruitment of PKC␦ may prevent PKC␦ from exerting its proapoptotic activity in the mitochondria (20,27), the localization of PKC␦ near the inclusions may also serve as a platform for Chlamydia to utilize the PKC␦ activity to facilitate chlamydial acquisition of host lipids. This hypothesis is supported by the finding that PKC␦ plays an essential role in various exocytosis processes, including antigen receptor-induced lytic degranulation (19), insulin secretion (28), and sphingomyelin transportation from the Golgi apparatus to the plasma membrane (29). In addition, PKC␦ can also activate the Raf-MEK-ERK-cPLA2 signaling pathway (17), which is required for chlamydial acquisition of glycerophospholipids from host cells (25).…”
supporting
confidence: 53%
“…Although the inclusion recruitment of PKC␦ may prevent PKC␦ from exerting its proapoptotic activity in the mitochondria (20,27), the localization of PKC␦ near the inclusions may also serve as a platform for Chlamydia to utilize the PKC␦ activity to facilitate chlamydial acquisition of host lipids. This hypothesis is supported by the finding that PKC␦ plays an essential role in various exocytosis processes, including antigen receptor-induced lytic degranulation (19), insulin secretion (28), and sphingomyelin transportation from the Golgi apparatus to the plasma membrane (29). In addition, PKC␦ can also activate the Raf-MEK-ERK-cPLA2 signaling pathway (17), which is required for chlamydial acquisition of glycerophospholipids from host cells (25).…”
supporting
confidence: 53%
“…ϩ CTL, we have recently shown that PKC ␦ is required for lytic granule exocytosis but is dispensable for activation, cytokine production, and expression of cytolytic molecules in response to TCR stimulation (16). We also showed that PKC ␦ does not regulate MTOC reorientation but is required for TCR-induced lytic granule polarization.…”
Section: G Ranule Exocytosis-mediated Cytotoxicity By Cd8mentioning
confidence: 85%
“…The cells in complete RPMI 1640 (10 7 cells/ml) were incubated for 30 min on ice in the presence or absence of 10 g/ml of purified anti-CD3 Ab followed by addition of 25 g/ml of goat anti-hamster IgG at 37°C for indicated periods of time. Cells were immediately lysed with ice-cold Lysis buffer (20 mM Tris-HCl (pH 7.5), 137 mM NaCl, 10% glycerol, 1% nonidet P-40, 2 mM EDTA, 1 mM PMSF, 2 mM Na 3 VO 4 , 10 mM NaF, and protease inhibitor mixture (Sigma-Aldrich)) for 30 min on ice and subjected to SDS-PAGE followed by immunobloting, as previously described (16).…”
Section: Activation Of Cd8 ϩ T Cells By Cd3 Crosslinking In Vitro; Immentioning
confidence: 99%
See 1 more Smart Citation
“…In exocytosis or degranulation, there is microtubules mobilization that leads the preformed granules or lysosomes of the cytotoxic cell towards the point of contact with the target cell, releasing stored lytic molecules (51,52). Degranulation can be detected by exposure of the lysosomal-membrane-associated glycoproteins, CD107a, CD107b, and CD63, on the lymphocyte surface (53).…”
Section: Granule-dependent Exocytosis Pathwaymentioning
confidence: 99%